2013
DOI: 10.1186/1472-6963-13-452
|View full text |Cite
|
Sign up to set email alerts
|

Changes in health care utilisation following a reform involving choice and privatisation in Swedish primary care: a five-year follow-up of GP-visits

Abstract: BackgroundThe organisation of Swedish primary health care has changed following introduction of free choice of provider for the population in combination with freedom of establishment for private primary care providers. Our aim was to investigate changes in individual health care utilisation following choice and privatisation in Swedish primary care from an equity perspective, in subgroups defined by age, gender and family income.MethodsThe study is based on register data years 2007 – 2011 from the Skåne Regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 20 publications
2
35
0
Order By: Relevance
“…). According to Beckman and Anell (), demand and expectations of welfare services will increase in pace with increases in the gross domestic product and household disposable income, as availability drives demand. However, most symptoms of illness are not presented to healthcare services (Elliott et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…). According to Beckman and Anell (), demand and expectations of welfare services will increase in pace with increases in the gross domestic product and household disposable income, as availability drives demand. However, most symptoms of illness are not presented to healthcare services (Elliott et al .…”
Section: Introductionmentioning
confidence: 99%
“…It is also economically beneficial for strained healthcare organizations to direct the management of minor illnesses away from high-cost settings . According to Beckman and Anell (2013), demand and expectations of welfare services will increase in pace with increases in the gross domestic product and household disposable income, as availability drives demand. However, most symptoms of illness are not presented to healthcare services (Elliott et al 2011), and minor illness is often managed through self-care interventions like watchful waiting, self-medication and rest (Gustafsson et al 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…[19,40] A study in Sweden showed that privatization of primary care providers improved patient accessibility, but only among people of high income. [7] …”
Section: Discussionmentioning
confidence: 99%
“…[4] Studies in Sweden, US, and Eastern European Countries demonstrated that privatization of healthcare has reduced public health service and care accessibility for vulnerable populations, diverting money to profitable services, and eventually driving up healthcare costs. [57] …”
Section: Introductionmentioning
confidence: 99%
“…In the period from 1997 to 2005, for the whole of Finland, there was a constant decrease in the number of visits to GPs in health centers per inhabitant over 65 years of age per year: from 4.3 (in 1997) to 3.2 visits per inhabitant (in 2005) [14], whereas in 2009 the same age group had only a mean of 2.4 GP visits per year [15]. In a Swedish study, over-65-year-old men had an average of 3.4-3.8 GP visits per year and women 4.2-4.5 GP visits per year in 2007-2011 [16]. The official statistics of Finnish health care services revealed that in 2001 the total number of visits to primary health services was 25,000,000.…”
Section: Introductionmentioning
confidence: 99%